Effects of L-Carnitine Pretreatment in Methamphetamine and 3-Nitropropionic Acid-Induced Neurotoxicity - BINIENDA, ZBIGNIEW K.; PRZYBYLA, BEATA D.; ROBINSON, BONNIE L.; SALEM, NADIA; VIRMANI, ASHRAF; AMATO, ANTONINO; ALI, SYED F. (Annals of the New York Academy of Sciences, 2006)
:  Adult, male Sprague‐Dawley rats were injected with 3‐ni‐tropropionic acid (3‐NPA) at 30 mg/kg or methamphetamine (METH) at 20 mg/kg alone or following pretreatment with L‐cartnitine (LC) at 100 mg/kg. Rectal temperature was measured before and 4 h following treatment. Animals were sacrificed at 4 h posttreatment. Monoamine neurotransmitters, dopamine (DA) and serotonin (5‐HT), and their metabolites were analyzed in the striatum using high‐performance liquid chromatography method coupled with electrochemical detection (HPLC/ED) . Transcripts of several genes related to DA metabolism were quantified using real time reverse transciption polymerase chain reaction (RT‐PCR). Core temperature decreased significantly after 3‐NPA acid and increased in METH‐treated rats (P < 0.05). Temperature change at 4 h exhibited a significant LC effect for 3‐NPA, preventing hypothermia (P < 0.05) and no effect for METH. Concentration of DA and 5‐HT, and their metabolites, 3,4‐dihydroxyphenylacetic acid (DOPAC), homovanillic acid (HVA), and 5‐hydroxyindoleacetic acid (5‐HIAA), increased significantly in 3‐NPA and decreased in METH‐treated rats. An increase in DOPAC/DA turnover and serotonin observed after 3‐NPA was abolished in LC‐/3‐NPA‐treated rats. In both 3‐NPA‐ and METH‐treated rats, LC prevented an increase in DA receptor D1 gene expression. It appears that carnitine effect preventing hypothermia after 3‐NPA treatments may be related not only to its mitochondriotropic actions but also to inhibitory effect on the DA and 5‐HT systems activated after the exposure to 3‐NPA. The same effect observed at the transcriptional level, at least for the DA receptor D1, may account for protection against METH toxicity.